Go in action - Kennedy, William (William Patrick); Ketelsen, Brian; Saint Martin, Erik (Manning Publications, 2016)
Go in Action introduces the Go language, guiding you from inquisitive developer to Go guru. The book begins by introducing the unique features and concepts of Go. Then, you'll get hands-on experience writing real-world applications including websites and network servers, as well as techniques to manipulate and convert data at speeds that will make your friends jealous. -- Provided by publisher.